A smart pH-switchable luminescent hydrogel - Zhang, Chunqiu; Li, Yiwei; Xue, Xiangdong; Chu, Pengfei; Liu, Chang; Yang, Keni; Jiang, Yonggang; Chen, Wei-Qiang; Zou, Guozhang; Liang, Xing-Jie (Chemical communications (Cambridge, England), 2015)
Here we report a novel example of a luminescent hydrogel, which is formed from silent individual molecules simply by altering the pH of the system. Formation of the emissive nanostructure is fully and repeatedly reversible. This hydrogel, with switchable luminescence, can potentially be used as a nano pH sensor.